2013
DOI: 10.1371/journal.pone.0084324
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Population of Epidermal Squamous Cell Carcinoma Cells with Enhanced Potential for Tumor Formation

Abstract: Epidermal squamous cell carcinoma is among the most common cancers in humans. These tumors are comprised of phenotypically diverse populations of cells that display varying potential for proliferation and differentiation. An important goal is identifying cells from this population that drive tumor formation. To enrich for tumor-forming cells, cancer cells were grown as spheroids in non-attached conditions. We show that spheroid-selected cells form faster growing and larger tumors in immune-compromised mice as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
176
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 54 publications
(184 citation statements)
references
References 61 publications
8
176
0
Order By: Relevance
“…We recently characterized epidermal cancer stem cells (ECS cells) and showed that ECS cells express stem cell markers characteristic of normal epidermal stem cells and embryonic stem cells (9). These ECS cells are able to generate tumors in immune-compromised mice following subcutaneous injection of as few as 100 cells (9). ECS cells express pluripotent markers, which are also expressed in esophageal and head/neck cancer stem cells (6, 10, 11).…”
Section: Introductionmentioning
confidence: 99%
“…We recently characterized epidermal cancer stem cells (ECS cells) and showed that ECS cells express stem cell markers characteristic of normal epidermal stem cells and embryonic stem cells (9). These ECS cells are able to generate tumors in immune-compromised mice following subcutaneous injection of as few as 100 cells (9). ECS cells express pluripotent markers, which are also expressed in esophageal and head/neck cancer stem cells (6, 10, 11).…”
Section: Introductionmentioning
confidence: 99%
“…As the epidermis protects the body from environmental insults, keratinocytes have a high risk of acquiring oncogenic mutations and undergoing uncontrolled proliferation, which is one of the hallmarks of cancer. Many epithelial cancers, including squamous cell carcinomas (SCCs), contain a minor population of tumorinitiating cells named cancer stem cells (CSCs) that can reconstitute and maintain the tumor (Adhikary et al, 2013;Patel et al, 2012;Thieu et al, 2013). CSCs share some characteristics of normal stem cells, give rise to heterogeneous tumors and are the source of metastatic outgrowths.…”
Section: Introductionmentioning
confidence: 99%
“…). This suggests that SCC-forming populations arises from both HF SCs and IFE SCs, although the relationship between the two populations in the pathogenesis of SCC is not well understood [23]. To dissect the contributions of these two populations of SCs to tumourigenesis, removing the IFE SC compartment while maintaining the HF SC compartment led to a reduction in the number of papillomas and SCCs compared to wild type mice, following wounding and subsequent administration of the tumour promoter, TPA [31].…”
Section: Squamous Cell Carcinoma Of the Skinmentioning
confidence: 99%